Experimental Study on the Vibration Characteristics of Dangerous Rock Mass under Constant Micromotion - Xiaoyong Zhang; Mowen Xie; Zhengjun Huang; Yan Du; Lei Zhang; Zhixiang Wu; Zhuang Fan (Advances in Civil Engineering)
In mountainous areas, dangerous rock mass collapse is a serious threat to human life and property safety. However, how to effectively prevent and control the instability of dangerous rock mass is still an urgent unsolved problem. In this study, the dynamic characteristics of dangerous rock mass under constant micromotion were analysed from the perspective of elastic wave propagation. When the slip plane of the dangerous rock mass is damaged, many micropores and cracks will appear in the medium composed of the slip surface. With constant micromotion as the vibration source, the elastic wave propagates to the dangerous rock mass through the damaged slip plane. The high-frequency components of elastic waves scatter in pores and fissures, where energy dissipates. According to this characteristic, a laboratory simulation experiment was designed. In the experiment, the damage process of the slip plane was simulated by the freeze‒thaw process of frozen hydrosol. The experimental analysis showed that the centre frequency of the high-frequency part of the dangerous rock mass model and bedrock mass model decreased as the frozen surface continued to melt. As the dangerous rock mass model and the bedrock mass model continued to fit, the centre frequency of the high-frequency part of the two rock mass models rebounded. This phenomenon showed that the damage degree of the slip plane between the dangerous rock mass and the bed rock mass can be effectively reflected by the centre frequency of the high-frequency part of the two rock mass models. During the experiment, the dangerous rock mass did not slide in the whole process, indicating that the deformation index has difficulty reflecting the stability of the hidden dangerous rock mass. In addition, the application conditions of using the natural frequency characteristics of dangerous rock mass and the scattering characteristics of elastic wave in the damage identification of structural plane were analysed: (1) when the structural plane has macrofracture, the change of natural frequency of dangerous rock mass should be used to analyse the damage degree of structural plane; (2) when there is no macrofracture of the structural plane, the characteristics of elastic wave scattering should be used to analyse the damage degree of the structural plane. This study provided a new idea for the prevention and control of dangerous rock masses and is expected to provide a useful reference for the automation of dangerous rock mass prevention and control.